2012
DOI: 10.1111/ane.12050
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment in stroke patients - a review

Abstract: Approximately 30% of all stroke patients suffer from post-stroke visual impairment. Hemianopia is the most common symptom, but also neglect, diplopia, reduced visual acuity, ptosis, anisocoria, and nystagmus are frequent. Partial or complete recovery of visual disorders can occur, but many patients suffer permanent disability. This disability is often less evident than impairment of motor and speech functions, but is negatively correlated with rehabilitation outcome and can lead to a significant reduction in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 31 publications
4
59
0
4
Order By: Relevance
“…These defects lead to impairments in activities of daily living such as reading, driving, or overall orientation (Kerkhoff, 1999). Besides the impaired overall well-being and quality of life (QoL), the risk for falling and trauma as well as social isolation in older patients increases (Timmis and Pardhan, 2012; Sand et al, 2013). In addition, the burden on the health care systems is tremendous since visually impaired patients are often unable to continue their occupation.…”
Section: Introductionmentioning
confidence: 99%
“…These defects lead to impairments in activities of daily living such as reading, driving, or overall orientation (Kerkhoff, 1999). Besides the impaired overall well-being and quality of life (QoL), the risk for falling and trauma as well as social isolation in older patients increases (Timmis and Pardhan, 2012; Sand et al, 2013). In addition, the burden on the health care systems is tremendous since visually impaired patients are often unable to continue their occupation.…”
Section: Introductionmentioning
confidence: 99%
“…This might be explained by the fact that the visual problems are less common compared to mobility and speech problems following stroke. In line with this, [23] reported that only 30% of the patients with stroke suffer visual problems. Hence, [24] mentioned that the rehabilitation needs to adapt to each patient's specific needs.…”
Section: Discussionmentioning
confidence: 52%
“…The most common visual disorders resulting from vascular-cerebral incidents found during routine clinical practice include [1,8]:…”
Section: Discussionmentioning
confidence: 99%